(untitled) (World Economics and Finance Bulletin, 2023)
This article analyzes the features of the development of the digital economy in our country, the tasks performed in this field, and the priority directions of the development of the field. Scientific proposals and practical recommendations developed in the course of research. Proposals have been developed to make the effective use of digital economy systems more effective in the country’s economic development.